2006
DOI: 10.1080/09513590601005409
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pregnancy outcomes and maternal vitamin D and calcium intake: A cross-sectional study

Abstract: Poor maternal vitamin D status affects fetal and infant skeletal growth. The aim of the present study was to determine the association between newborn outcomes and maternal calcium and vitamin D intakes. Four hundred and forty-nine pregnant women, healthy at the point of delivery, and their newborns were enrolled in the study, which was performed in three university hospitals in Tehran in March 2004. Maternal anthropometric data and energy, protein, calcium and vitamin D intakes were collected, and newborn out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 30 publications
4
71
3
Order By: Relevance
“…No effect of maternal vitamin D levels on neonatal birth weight was detected in a sample of 50 mothers-neonates from Iran after adjusting for maternal height, age, and parity [112]. Conversely, in a larger sample of 449 women and their newborns from Tehran, neonates of mothers with adequate calcium and vitamin D intake were 0.9 cm taller and had a better Apgar at birth [119]. Vitamin D supplementation for 1 year increased lean mass, bone area, and bone mass in a randomised controlled trial in Lebanese adolescent girls [92].…”
Section: Middle East and Africamentioning
confidence: 99%
“…No effect of maternal vitamin D levels on neonatal birth weight was detected in a sample of 50 mothers-neonates from Iran after adjusting for maternal height, age, and parity [112]. Conversely, in a larger sample of 449 women and their newborns from Tehran, neonates of mothers with adequate calcium and vitamin D intake were 0.9 cm taller and had a better Apgar at birth [119]. Vitamin D supplementation for 1 year increased lean mass, bone area, and bone mass in a randomised controlled trial in Lebanese adolescent girls [92].…”
Section: Middle East and Africamentioning
confidence: 99%
“…In Brazil, other studies involving samples of different population groups have found similar "healthy" 23,24 or "cautious" 22 patterns. Research with pregnant women from Finland and England also identified "healthy" and "health conscious" varied patterns 1,2,3,4,5,6,8,9,10,11,19,41,42 .…”
Section: Characteristicmentioning
confidence: 99%
“…Research has demonstrated that healthy eating habits during pregnancy affect fetal development and contribute to prevent pregnancy complications 5,6 and the occurrence of diseases in adulthood 7 . An appropriate diet helps recovery from childbirth and favors breastfeeding 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a cross-sectional study, including 449 pregnant women, maternal calcium and vitamin D intake was associated with weight gain of mothers during pregnancy, as well as birth weight and 1-min Apgar score. 25 Until now, no firm data have answered the question of whether pregnancy and lactation lead to an increased need for vitamin D. 26 --28 In order to study possible effects of P-25OHD concentration on human fertility and pregnancy outcome, we recruited healthy young Danish women, with immediate plans for pregnancy. Within this cohort, we studied the effects of pre-conceptional P-25OHD concentration on chances for pregnancy, as well as the effects of P-25OHD concentration during pregnancy on the risk of miscarriage and pregnancy outcomes in term of birth weight, birth length, head circumference and Apgar score.…”
Section: Introductionmentioning
confidence: 99%